cProgress towards the development of a chemosensory-based biotic ligand model in fathead minnows (Pimephales promelas) and wild yellow perch (Perca flavescens) - Green, Warren W. (My University, 2007)
Elevated metal concentrations in the aquatic environment may pose a threat to fishes through acute lethal and chronic sub-lethal exposures. To assess the impact of anthropogenic metal contamination on aquatic fauna the Biotic Ligand Model (BLM), a model based on metal-binding to the gills, is now considered to be the best approach for predicting site-specific metal toxicity. The olfactory epithelium (OE) of fishes is exposed directly to the aquatic environment and is vulnerable to waterborne exposures to sublethal metal concentrations. These exposures have been shown to impair the olfactory function of fishes. The goal of this thesis was to begin the development of a chemosensory-based BLM (cbBLM) to predict sub-lethal metal toxicity using laboratory based experiments with fathead minnows (Pimephales promelas, FHM) and yellow perch (Percaflavescens, YP), the latter chronically exposed to metals in the wild. Our results demonstrate that Cu and Cd binding to the OE of fathead minnows was saturable and that increasing waterborne Ca decreases metal accumulation in the OE. The binding of Cd to the OE of wild yP was saturable but the binding of Cu was not. Acute exposure of the OE to Cu impaired peripheral olfactory function in FHM as demonstrated by a decreased electrophysiological response but this was not observed for exposures to Cd. Moreover, the peripheral and central olfactory system functions of chronically metal-exposed wild YP were also impaired as indicated by an elevated electrophysiological response and a lack of behavioural response to conspecific skin extracts. This is the first study to examine the binding characteristics of Cu and Cd to the OE of fishes and to relate this metal accumulation in the OE to the impairment of peripheral olfactory function. This information can now be used to begin development of a cbBLM. A cbBLM would use metal-OE binding constants, site-specific water chemistry, and ethological or ecological endpoints. Such models would be useful in devising environmental regulations to predict and therefore prevent chronic, sub-lethal metal toxicity in fishes and improve ecological risk assessment.
Keywords: Biology; Biology